Finite element software for microwave engineering - Itoh, Tatsuo; Pelosi, Giuseppe; Silvester, P.P (Wiley series in microwave and optical engineering, 1996)
This book presents an overview of finite element software. It discusses the capabilities and limitations of the available softwear and helps readers formulate engineering problems so that they fit into the framework of current software.